2013
DOI: 10.2139/ssrn.2373214
|View full text |Cite
|
Sign up to set email alerts
|

Fertilizer in Ethiopia: An Assessment of Policies, Value Chain, and Profitability

Abstract: The International Food Policy Research Institute (IFPRI), established in 1975, provides evidence-based policy solutions to sustainably end hunger and malnutrition and reduce poverty. The Institute conducts research, communicates results, optimizes partnerships, and builds capacity to ensure sustainable food production, promote healthy food systems, improve markets and trade, transform agriculture, build resilience, and strengthen institutions and governance. Gender is considered in all of the Institute's work.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 44 publications
(30 citation statements)
references
References 27 publications
0
27
0
Order By: Relevance
“…The use of the primary fertility-enhancing agricultural technologies such as irrigation, fertilizers and pesticides is lower than in other regions of the developing world, sharply limiting yield gains. Rashid et al (2013) indicate that only 19 percent of total cultivated area is fertilized, although Amhara, the region of this project, exhibits somewhat higher input use than the Ethiopian national average. They also show that cereals, especially teff, are the main crops that receive fertilizer.…”
Section: Inputs and Credit In Ethiopian Smallholder Agriculturementioning
confidence: 82%
“…The use of the primary fertility-enhancing agricultural technologies such as irrigation, fertilizers and pesticides is lower than in other regions of the developing world, sharply limiting yield gains. Rashid et al (2013) indicate that only 19 percent of total cultivated area is fertilized, although Amhara, the region of this project, exhibits somewhat higher input use than the Ethiopian national average. They also show that cereals, especially teff, are the main crops that receive fertilizer.…”
Section: Inputs and Credit In Ethiopian Smallholder Agriculturementioning
confidence: 82%
“…These will require addressing some of the remaining handicaps that reduce farmer access to modern varieties, inputs and services. Some of the institutional and policy issues raised by several authors, especially around the seed system (e.g., Alemu 2010;Alemu et al 2010;Dorosh and Rashid 2013;Rashid et al 2013;Spielman et al 2013), have been changing, albeit slowly, through partnerships with the national program and regional initiatives such as DTMA, Program for Africa's Seed Systems (PASS), and other bilateral programs. We highlight below some of the key issues, including the need for variety replacement, addressing issues related to seed systems, raising the level of input use, and maintaining a critical mass of researchers.…”
Section: Conclusion and Policy Implicationsmentioning
confidence: 99%
“…As reported by Heisey and Norton (2007), these margins in Ethiopia compare favourably with other African countries, though are still higher than in Asian and Latin American countries. Similarly, Rashid et al (2013) showed that fertilizer prices in Ethiopia are significantly lower than in neighbouring Kenya, Uganda, Rwanda and Tanzania. An explanation for such "low" prices is the state control over prices and marketing margins.…”
Section: Discussionmentioning
confidence: 99%